The technique of walking bass case study: the comparison between Zailan Razak and Ruslan imam in the song 'lihatlah' by Ahmad Jaafar / Shah Herwan Superdi - Superdi, Shah Herwan (2009)
The main objective in conducting this research is to compare the technique of walking bass between these two bassists, Ruslan Imam and Zailan Razak. Walking bass is a technique of playing movement line that is created from scale and chord tone. Besides that, there are other approaches those are chromatic approach, passing tone and ghost note which will make a strong walking bass line. For the purpose of this fundamental research topic, the song Lihatlah by Ahmad Jaafar has been using for this research. The reason as to the song been chosen is because this song is one of the earliest jazz song in Malaysia.